Base formativa do docente da educação básica no pós-março de 2020: conexões com tecnologias - Nikolay, Liamara da Cunha (2023)
The present study is part of the research group "Innovative and Active Hybrid Perspectives in the Educational Context Post-March 2020" of the Professional Master's Program in Education and New Technologies at UNINTER. It is guided by the focus that, with the COVID-19 pandemic, educational institutions were compelled to adopt remote and hybrid approaches, demanding a quick adaptation from teachers. The interconnection between teacher training and educational technologies proved to be essential to meet contemporary demands. Thus, the objective is to design a framework for the meaningful use of digital technologies in the daily life of Basic Education teachers, based on teachers' perspectives on pedagogical, content, and technological knowledge from a private education network in southern Brazil. The research was divided into four methodological stages. The first phase involved a literature review, crucial for situating the study, identifying gaps in the theme, and grounding theoretical and methodological approaches. The systematic literature review highlighted the relationship between teacher training and the use of technologies before, during, and after the COVID-19 pandemic in the Brazilian context, as well as the beliefs of Basic Education teachers regarding their formative needs. The second stage, empirical research, was based on a mixed quantitative-qualitative approach. Using a questionnaire administered to Basic Education teachers in a private education network in southern Brazil, the aim was to understand educators' beliefs regarding their training in technological contexts. The third stage focused on describing and analyzing the collected data. With 141 respondents from the states of Santa Catarina, Rio Grande do Sul, and Paraná, the researcher used Google Forms for data collection. The quantitative part included data analysis through graphs and descriptive statistics, while the qualitative part was not explicitly mentioned in the abstract. These stages allowed the researcher to explore participants' responses, gaining a better understanding of teachers' beliefs and needs regarding teacher training, technology use, and pandemic scenarios. The study originates a structured framework in "A4," meaning four guiding connections that address essential aspects of pedagogical integration of technology for teaching: 1- technological approach; 2 – curricular application; 3 – holistic approach; 4 – active learning.